The application of the services of the social security administration agency in Hospitals in the perspective of the national social security system - Wiwin Triyunarti; Rukmana Amanwinata; I Gde Pantja Astawa (Magister Kenotariatan Universitas Pasundan, 2022)
The relationship between the parties is a relationship based on law. Social security must cooperate with hospitals. Social security participants can use these hospitals under a tiered referral system, except in emergencies. This research examines the law conceptualized as norms or rules that apply in society by using a juridical approach through a statutory procedure, historical method, philosophical approach, and futuristic approach. Sources of data obtained using literature studies this literature study is carried out to find secondary data related to conceptions, theories, and opinions related to the problem under study. From the research, the state guarantees all cost difficulties, improves health services, and improves health status by implementing Universal Health Coverage. The ease of the treatment process using insurance is considered a significant benefit as a manifestation of the mandate of the Constitution. The guarantee of health costs for the community is realized in health financing. The government can also control the quality and cost of health organized by hospitals considering the impact received by the community as service recipients.